(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the peculiarities of functioning of Ukrainian microtoponyms of the Uzh river basin, that are based on the geographical terms. Connection between the microtoponymic system of the region, its geographical environment is established. Basic semantic groups are analyzed.